2011
DOI: 10.1029/2011gc003839
|View full text |Cite
|
Sign up to set email alerts
|

Seismic triggering of landslides and turbidity currents offshore Portugal

Abstract: [1] Sediments in deep water basins often include turbidites that record sediment input from adjacent continental margins. In seismically active areas, where turbidity currents are triggered by earthquakes, the basinal turbidite sequence may thus contain a record of palaeoseismicity, which can be used to infer the frequency of earthquakes affecting the margins of the basin. This is particularly useful where large earthquakes have a recurrence interval than is greater than the historical record. However, turbidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…If such a link between sea level and landslide frequency exists it is too weak to be detected using the available global data base. It is possible that controlling factors vary between different geographical areas, and their role is therefore hidden Stigall and Dugan, 2010;Masson et al, 2011). These hypotheses are 20 poorly tested, and even less is known about the effect of other preconditioning 21 factors such as fluid flow focussing in the slope (Dugan, 2012).…”
mentioning
confidence: 99%
“…If such a link between sea level and landslide frequency exists it is too weak to be detected using the available global data base. It is possible that controlling factors vary between different geographical areas, and their role is therefore hidden Stigall and Dugan, 2010;Masson et al, 2011). These hypotheses are 20 poorly tested, and even less is known about the effect of other preconditioning 21 factors such as fluid flow focussing in the slope (Dugan, 2012).…”
mentioning
confidence: 99%
“…Based on the turbidite frequency, Gràcia et al (2010) proposed a recurrence interval of approximately 2,000 years for the large earthquakes. Masson et al (2011) presented further compelling evidence of seismic triggering of landslides and turbidity currents along the SW Iberian margin. Their study demonstrated that turbidites emplaced at 6,600 and 8,300 cal yr BP on the TAP correlate with erosional hiatuses in two submarine canyons on the continental margin.…”
Section: Introductionmentioning
confidence: 99%
“…There is extensive evidence of mass movements associated with these faults, as demonstrated throughout this work. Several studies in the area have considered landslides and turbidite records as proxies of paleoseismic activity (Gràcia et al 2010;Masson et al 2011). Recently, deep drilling during IODP Expedition 339 at Site U1391 revealed the existence of several debris flow events interbedded within the sedimentary succession of the Alentejo margin (Hernández-Molina et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations